Tenascin-C in betel-quid associated lesions - Zain, R.B.; Fukano, H.; Ikeda, N.; Kudeken, W.; Shrestha, P.; Ghazali, M.N.; Takai, Y.; Mori, M. (1999)
The expression of Tenascin-C, an adhesion modulating or anti- adhesive extracellular matrix protein, was evaluated in betel quid associated lesions of oral mucosa showing focal hyperkeratosis (n=15), dysplasia (n=15), oral submucous fibrosis (n=7) and oral squamous cell carcinoma (n=8). All the patients were chewers of betel quid containing betel leaves, areca nuts, lime and tobacco. The results obtained from this study were compared to similar lesions in smokers and non-quid users cited in the literature (Shrestha et al, Oral Oncol, 1994). An enhanced expression of TN-C was observed in epithelial connective tissue interface of quid associated hyperkeratotic and dyplastic mucosa. However, the expression was less extensive as compared to similar lesions among smokers or those without smoking or quid habits although the enhanced expression observed in the stromal tissue surrounding the carcinoma cells in carcinoma arising at sites where quids were often placed did not differ. Oral submucous fibrosis showed no or a faint linear immunoreactivity to an intense reactivity often abruptly ending at the epithelial-connective tissue interface. Areas of subepithelial hyalinization in oral submucous fibrosis remained unreactive. These variations in oral submucous fibrosis were observed in different areas of the same specimen. Oral squamous cell carcinoma, however, showed no difference in the expression of TN-C among these two groups of patients. The result of the present study suggest that epithelial hyperproliferation with or without dysplastic changes in quid related oral lesions may induce an altered epithelial-mesenchymal interactions and may be a factor in an enhanced expression of TH-C. However, the reaction products may be less widespread as compared to lesions among smokers or those without smoking or quid habits